Short- and long-term stroboscopic training effects on visuomotor performance in elite youth sports. part 1: reaction and behavior - Hülsdünker, T.; Gunasekara, N.; Mierau, A. (Medicine & Science in Sports & Exercise, 2021)
Purpose Recent research suggests that stroboscopic training is an effective tool to improve visual and visuomotor performance. However, many studies were limited by small samples, short training interventions, inexperienced athletes, and an exclusive focus on short-term effects. This first part of the study evaluates the short- and long-term effects of stroboscopic training on visuomotor reaction speed in elite athletes.